Isolating membrane, preparation method thereof, and related secondary battery and electric device
By applying nanocellulose on the isolation film of the secondary battery and reasonably controlling the surface tension, combined with the use of fillers and adhesives, the problem of insufficient heat resistance of the isolation film is solved, and the thermal safety performance and energy density of the battery are improved. .
Patent Information
- Application Number
- CN202411413925.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2022-08-15
- Publication Date
- 2025-01-07
AI Technical Summary
The insulation film of existing secondary batteries has poor heat resistance, resulting in insufficient thermal safety performance and affecting the safety performance and service life of the battery.
The nanocellulose coating is coated with a porous substrate surface. By reasonably controlling the surface tension ratio of the porous substrate and the coating, the heat resistance and viscosity strength of the isolation film are improved, and the selection of fillers and binders is achieved to form a stable The spatial network structure is used to improve the wettability of the electrolyte and the ion transport characteristics.
It achieves excellent heat resistance and high viscosity strength of the isolation film. The secondary battery takes into account high energy density, high thermal safety performance and long service life.
Smart Images

Figure CN119275491A_ABST
Abstract
Description
[0001] This application is a divisional application based on the invention with application number 202280018819.3, application date August 15, 2022, applicant Contemporary Amperex Technology Co., Ltd., and invention name “Isolation membrane, preparation method thereof, and related secondary batteries and electrical devices”. Technical Field
[0002] The present application belongs to the field of battery technology, and specifically relates to an isolation membrane, a preparation method thereof, and related secondary batteries and electrical devices. Background Art
[0003] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. With the application and promotion of secondary batteries, their safety issues, especially thermal safety issues, have received more and more attention. The isolation membrane is one of the main components that affect the safety performance of secondary batteries. How to provide an isolation membrane with excellent heat resistance and stable structure is still a key challenge in this field. Summary of the invention
[0004] The purpose of the present application is to provide an isolation membrane, a preparation method thereof, and related secondary batteries and electrical devices. The isolation membrane has the characteristics of excellent heat resistance and high viscosity strength, so that the secondary battery using the isolation membrane can have high energy density, high thermal safety performance and long service life.
[0005] In a first aspect, the present application provides an isolation membrane, comprising a porous substrate and a coating disposed on at least one surface of the porous substrate, wherein the coating comprises nanocellulose, the surface tension of the porous substrate is δ1mN / m, the surface tension of the coating is δ2mN / m, and the isolation membrane satisfies δ1≥23 and 25≤δ2≤50.
[0006] When the surface tension of the porous substrate is within an appropriate range, the coating slurry is not easily missed during coating, and the porous substrate covers a larger area, so that the isolation membrane can have better heat resistance and the secondary battery can have better safety performance; at the same time, it is also beneficial to maintain the bonding strength between the porous substrate and the coating within a higher range, greatly reducing the risk of coating falling off.
[0007] When the surface tension of the coating is within an appropriate range, it is beneficial to maintain the bonding strength between the porous substrate and the coating within a higher range, greatly reducing the risk of coating shedding; it is also beneficial for the electrolyte to infiltrate the isolation membrane, improve the ion transmission properties of the isolation membrane, and improve the capacity performance characteristics of the secondary battery.
[0008] In any embodiment of the present application, 23≤δ1≤45, optionally, 25≤δ1≤45. When the surface tension of the porous substrate is within a suitable range, the coating slurry is not easily missed during coating, and the porous substrate has a larger coverage area, so that the separator can have better heat resistance and the secondary battery can have better safety performance; at the same time, it is also beneficial to keep the bonding strength between the porous substrate and the coating within a higher range.
[0009] In any embodiment of the present application, 30≤δ2≤45, optionally, 30≤δ2≤43. When the surface tension of the coating is within a suitable range, it is beneficial to maintain the bonding strength between the porous substrate and the coating within a relatively high range; it is also beneficial for the electrolyte to infiltrate the isolation membrane, improve the ion transport properties of the isolation membrane, and improve the capacity performance characteristics of the secondary battery.
[0010] In any embodiment of the present application, 0.68≤δ1 / δ2≤1.8, and optionally, 0.7≤δ1 / δ2≤1.2. Thus, the separator can better balance the characteristics of excellent heat resistance, high viscosity strength and good ion transport properties, so that the secondary battery using the separator can better balance high energy density, high thermal safety performance and long service life.
[0011] In any embodiment of the present application, the nanocellulose includes at least one of unmodified nanocellulose and modified nanocellulose, and may be modified nanocellulose.
[0012] In any embodiment of the present application, the modified nanocellulose includes a modification group, and the modification group includes at least one of an amino group, a carboxylic acid group, an aldehyde group, a sulfonic acid group, a boric acid group, and a phosphoric acid group, and optionally includes at least one of a sulfonic acid group, a boric acid group, and a phosphoric acid group. When the nanocellulose has the above-mentioned specific modification group, on the one hand, it can effectively improve the heat resistance of the isolation membrane and the thermal safety performance of the secondary battery, and on the other hand, it is also conducive to maintaining the bonding strength between the porous substrate and the coating within a high range.
[0013] In any embodiment of the present application, the modified nanocellulose includes a hydroxyl group and a modified group, and the molar ratio of the modified group to the hydroxyl group is 1:4 to 4:1, and can be 2:3 to 7:3. When the molar ratio of the modified group to the hydroxyl group is within a suitable range, the heat resistance and ion transport properties of the separator can be further improved, and the separator can also have high bonding strength.
[0014] In any embodiment of the present application, the average diameter of the nanocellulose is ≤40 nm, and can be 10 nm to 35 nm. When the average diameter of the nanocellulose is within a suitable range, the heat resistance of the separator can be further improved and the heat shrinkage of the separator can be reduced.
[0015] In any embodiment of the present application, the average length of the nanocellulose is 100 nm to 600 nm, and can be optionally 200 nm to 500 nm. When the average length of the nanocellulose is within a suitable range, the heat resistance and ion transport properties of the separator can be further improved.
[0016] In any embodiment of the present application, the aspect ratio of the nanocellulose is 5 to 60, and can be 15 to 30. When the aspect ratio of the nanocellulose is within a suitable range, the ion transport properties of the separator can be further improved.
[0017] In any embodiment of the present application, the content of the nanocellulose in the coating is ≥8 wt %, optionally 10 wt % to 25 wt %, based on the total weight of the coating.
[0018] When the content of nanocellulose is within an appropriate range, it can ensure that the coating slurry has an appropriate viscosity, which is more conducive to coating, and can also maintain a high bonding strength between the coating and the porous substrate, thereby improving the structural stability of the isolation membrane; in addition, it is also beneficial for nanocellulose and other components (such as fillers, etc.) to build a stable spatial network structure, thereby further improving the performance of the isolation membrane.
[0019] In any embodiment of the present application, the coating layer further includes a filler, and the filler includes at least one selected from inorganic particles and organic particles.
[0020] In any embodiment of the present application, the content of the filler in the coating is ≥60 wt %, optionally 65 wt % to 90 wt %, based on the total weight of the coating.
[0021] In any embodiment of the present application, the filler includes primary particles, secondary particles or a combination thereof. Optionally, the filler includes at least secondary particles.
[0022] The filler with secondary particle morphology has a smaller particle size, a larger specific surface area, and a better affinity with nanocellulose. At the same time, nanocellulose can also be overlapped in the gaps between the primary particles that constitute the filler with secondary particle morphology, so that the nanocellulose and the filler with secondary particle morphology are overlapped to form an integrated effect. As a result, the coating can have a more stable spatial network structure, thereby further improving the performance of the isolation membrane.
[0023] The filler with primary particle morphology has a larger particle size and higher strength, which can better play a skeleton support role in the coating, reduce the amount of binder, reduce the thermal shrinkage of the isolation membrane and improve the heat resistance of the isolation membrane; and it also helps to make the coating have more pore structure and less water content when the amount is small, which can further improve the ion transmission properties of the isolation membrane and the wetting properties of the electrolyte.
[0024] In any embodiment of the present application, the average particle size Dv50 of the filler having the primary particle morphology is from 100 nm to 800 nm, and can be optionally from 200 nm to 400 nm.
[0025] In any embodiment of the present application, the average particle size Dv50 of the filler having the secondary particle morphology is ≤200 nm, and can be optionally 50 nm to 200 nm.
[0026] In any embodiment of the present application, the filler includes inorganic particles in a primary particle morphology, inorganic particles in a secondary particle morphology, or a combination thereof. Optionally, the filler includes at least inorganic particles in a secondary particle morphology.
[0027] In any embodiment of the present application, the crystal form of the inorganic particles in the primary particle morphology includes at least one of an α crystal form and a γ crystal form, and optionally includes an α crystal form.
[0028] In any embodiment of the present application, the crystal form of the inorganic particles with secondary particle morphology includes at least two of the α crystal form, the θ crystal form, the γ crystal form and the η crystal form, and optionally includes at least two of the α crystal form, the θ crystal form and the γ crystal form.
[0029] In any embodiment of the present application, the coating further comprises a non-granular binder, and optionally, the non-granular binder comprises an aqueous solution binder, which is beneficial for the preparation and coating of the coating slurry.
[0030] In any embodiment of the present application, the content of the non-granular binder in the coating is less than 1wt%, based on the total weight of the coating. The isolation membrane provided by the present application can reduce the amount of binder while maintaining high bonding strength and good ion transmission properties.
[0031] In any embodiment of the present application, the coating does not contain a wetting agent, thereby avoiding the problem of pore blocking of the porous substrate during coating and drying of the coating slurry.
[0032] In any embodiment of the present application, the thickness of the porous substrate is ≤6 μm, and may be 3 μm to 5 μm, which helps to improve the energy density of the secondary battery.
[0033] In any embodiment of the present application, the surface density of the coating is 0.6 g / m 2 Up to 1.5g / m 2 , optional 0.8g / m 2 Up to 1.1g / m 2 This makes it possible to obtain an isolation membrane with better heat resistance and ion transport properties.
[0034] In any embodiment of the present application, the thickness of the coating is ≤1.5 μm, and can be 0.5 μm to 0.8 μm, thereby helping to improve the energy density of the secondary battery.
[0035] In any embodiment of the present application, the isolation film further includes an adhesive layer, the adhesive layer is disposed on at least a portion of the surface of the coating, the adhesive layer includes a granular binder, and optionally, the granular binder includes at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer. The adhesive layer can not only prevent the coating from falling off and improve the safety performance of the secondary battery, but also improve the interface between the isolation film and the electrode and enhance the cycle performance of the secondary battery.
[0036] In any embodiment of the present application, the bonding strength between the coating and the porous substrate is 16 N / m to 40 N / m, and optionally 20 N / m to 35 N / m.
[0037] In any embodiment of the present application, the longitudinal heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤5%, and can be optionally 0.5% to 3%.
[0038] In any embodiment of the present application, the transverse heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤5%, and can be optionally 0.5% to 3%.
[0039] In any embodiment of the present application, the longitudinal tensile strength of the isolation film is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 .
[0040] In any embodiment of the present application, the transverse tensile strength of the separator is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 .
[0041] In any embodiment of the present application, the wetted length of the isolation membrane is ≥30 mm, and can be optionally 30 mm to 80 mm.
[0042] In any embodiment of the present application, the wetting speed of the isolation film is ≥3 mm / s, and can be optionally 3 mm / s to 10 mm / s.
[0043] In any embodiment of the present application, the air permeability of the isolation membrane is ≤300s / 100mL, and can be optionally 100s / 100mL to 230s / 100mL.
[0044] When the performance of the separator satisfies one or more of the above conditions, it is beneficial to improve at least one of the energy density, thermal safety performance, capacity utilization characteristics and service life of the secondary battery.
[0045] The second aspect of the present application provides a method for preparing the isolation membrane of the first aspect of the present application, comprising the following steps: S1, providing a porous substrate; S2, providing a coating slurry containing nanocellulose; S3, coating the coating slurry on at least one surface of the porous substrate to form a film layer and drying to obtain an isolation membrane, wherein the isolation membrane comprises a porous substrate and a coating arranged on at least one surface of the porous substrate, the surface tension of the porous substrate is δ1mN / m, the surface tension of the coating is δ2mN / m, and the isolation membrane satisfies δ1≥23 and 25≤δ2≤50.
[0046] In any embodiment of the present application, the coating slurry further comprises a filler.
[0047] In any embodiment of the present application, the surface tension of the coating slurry is 18 mN / m to 52 mN / m.
[0048] In any embodiment of the present application, the method further comprises the following steps: S4, secondary coating: coating a slurry containing a granular binder on at least a portion of the surface of the coating layer, and forming an adhesive layer after drying.
[0049] The preparation method of the isolation film of the present application obtains the coating layer by one-time coating, which greatly simplifies the production process of the isolation film.
[0050] A third aspect of the present application provides a secondary battery, comprising the isolation film of the first aspect of the present application or the isolation film prepared by the method of the second aspect of the present application.
[0051] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application.
[0052] The isolation film provided in the present application has the characteristics of excellent heat resistance and high viscosity strength, so that the secondary battery using the isolation film can have high energy density, high thermal safety performance and long service life. The electrical device of the present application includes the secondary battery provided in the present application, and thus has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0054] Figure 1 It is a schematic diagram of one embodiment of the secondary battery of the present application.
[0055] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a secondary battery.
[0056] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.
[0057] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0058] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0059] Figure 6 It is a schematic diagram of one embodiment of an electric device including the secondary battery of the present application as a power source.
[0060] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 secondary battery, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION
[0061] Hereinafter, the isolation membrane of the present application, its preparation method, and the embodiments of the related secondary battery and electrical device are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0062] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0063] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0064] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0065] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0066] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0067] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0068] In the present application, the terms "plurality" and "multiple" refer to two or more.
[0069] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.
[0070] Unless otherwise specified, the values of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0071] Generally, a secondary battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass freely to form a loop. Therefore, the stability of the separator, especially the thermal stability and structural stability, will directly affect the safety performance of the secondary battery.
[0072] The inventors of the present application surprisingly discovered during the research process that by providing a coating containing nanocellulose on the surface of the porous substrate of the isolation membrane and rationally controlling the ratio of the surface tension of the porous substrate and the surface tension of the coating within an appropriate range, the isolation membrane can have both excellent heat resistance and high viscosity strength, thereby allowing the secondary battery using the isolation membrane to have high energy density, high thermal safety performance and long service life.
[0073] Isolation film
[0074] Specifically, the first aspect of the embodiment of the present application provides a separator, comprising a porous substrate and a coating disposed on at least one surface of the porous substrate, wherein the coating comprises nanocellulose, the surface tension of the porous substrate is δ1mN / m, the surface tension of the coating is δ2mN / m, and the separator satisfies δ1 / δ2≥0.68
[0075] At present, the separator used in commercial secondary batteries is usually a polyolefin film, such as a polyethylene film, a polypropylene film or a polypropylene / polyethylene / polypropylene three-layer composite film, whose melting point is between 130°C and 160°C, so the heat resistance of the separator is poor, and it will shrink severely when heated, increasing the risk of short circuit between the positive and negative electrodes. Coating a heat-resistant inorganic ceramic layer on a porous substrate (such as a polyolefin film, a non-woven fabric, etc.) can improve the heat resistance of the separator, but due to the large particle size of commercially available inorganic ceramic particles, the number of layers accumulated on the porous substrate is small (usually ≤5 layers), which leads to limited improvement in the heat resistance of the separator, and also increases the overall thickness of the separator, resulting in the inability to balance the energy density of the secondary battery, especially in the field of power batteries, which is not conducive to the improvement of the cruising range. In addition, the bonding strength between the inorganic ceramic layer and the porous substrate is also poor. During the long-term charging and discharging process of the secondary battery, the risk of the inorganic ceramic layer falling off after being immersed in the electrolyte is high.
[0076] Nanocellulose refers to the general term for cellulose with any dimension at the nanometer level (e.g., within 100nm). It has both the characteristics of cellulose and the characteristics of nanoparticles. It can be a polymer nanomaterial extracted from wood, cotton, straw, etc. in nature by one or more means of chemistry, physics, biology, etc. It has the advantages of wide sources, low cost, biodegradability, high modulus, and high specific surface area. Therefore, it is an excellent substitute for traditional petrochemical resources and can effectively alleviate environmental pollution and petrochemical resource shortages. Nanocellulose also has good high temperature resistance and a small volume change after heating, which can improve the heat resistance of the separator, reduce the degree of shrinkage of the separator when heated, reduce the risk of short circuit between the positive and negative electrodes, and make the secondary battery have high thermal safety performance. Compared with traditional inorganic ceramic particles, nanocellulose has a lower density, which can also reduce the weight of the secondary battery.
[0077] Therefore, when the coating of the present application includes nanocellulose, it helps to improve the heat resistance of the separator, and compared with the traditional inorganic ceramic layer, the coating of the present application also has a smaller thickness and weight, which also helps to improve the volume energy density and weight energy density of the secondary battery. In addition, since the coating of the present application has high heat resistance, a thinner porous substrate can be selected, which can further reduce the weight of the secondary battery and improve the volume energy density and weight energy density of the secondary battery.
[0078] The inventors of the present application discovered during the research process that when a coating slurry containing nanocellulose is coated on the surface of a porous substrate, it is easy to cause coating leakage, thereby reducing the mechanical strength of the prepared isolation membrane and increasing the risk of short circuit between the positive and negative electrodes.
[0079] The inventor of the present application surprisingly found in the research process that by making the surface tension δ1mN / m of the porous substrate and the surface tension δ2mN / m of the coating (both refer to the dried coating in the present application) satisfy δ1 / δ2≥0.68, the porous substrate and the coating can have a high bonding strength, thereby avoiding the problem of coating shedding during the long-term charging and discharging of the secondary battery; at the same time, it can also avoid the problem of coating leakage during the coating slurry coating, so that the coating also has the characteristics of high uniformity and high porous substrate coverage, and thus the isolation membrane can have excellent heat resistance. When the surface tension of the porous substrate is low and the surface tension of the coating is high, resulting in δ1 / δ2 being less than 0.68, the problem of coating leakage is prone to occur during the coating slurry coating. At this time, the isolation membrane has poor heat resistance and poor bonding strength, and the risk of coating shedding is high during the long-term charging and discharging of the secondary battery.
[0080] Therefore, the isolation film provided in the present application has the characteristics of excellent heat resistance and high viscosity strength, so that the secondary battery using the isolation film can have high energy density, high thermal safety performance and long service life.
[0081] The inventors of the present application were also surprised to find during the research process that the ratio of the surface tension of the porous substrate to the surface tension of the coating should not be too high. At this time, the air permeability and ion transmission characteristics of the isolation membrane may deteriorate, thereby affecting the electrochemical and kinetic properties of the secondary battery, for example, affecting the cycle performance of the secondary battery. In some embodiments, optionally, 0.68≤δ1 / δ2≤1.8, 0.7≤δ1 / δ2≤1.5, 0.7≤δ1 / δ2≤1.2, 0.7≤δ1 / δ2≤1.0 or 0.7≤δ1 / δ2≤0.9. As a result, the isolation membrane can better balance the characteristics of excellent heat resistance, high viscosity strength and good ion transmission characteristics, so that the secondary battery using the isolation membrane can better balance high energy density, high thermal safety performance and long service life.
[0082] In some embodiments, the surface tension δ1mN / m of the porous substrate may satisfy δ1≥23, optionally, 23≤δ1≤45. When the surface tension of the porous substrate is within a suitable range, the coating slurry is not easily leaked during coating, and the porous substrate has a larger coverage area, so that the separator can have better heat resistance and the secondary battery can have better safety performance; at the same time, it is also beneficial to keep the bonding strength between the porous substrate and the coating within a high range, greatly reducing the risk of coating shedding.
[0083] In some embodiments, the surface tension δ2mN / m of the coating may satisfy 25≤δ2≤50, and optionally, 30≤δ2≤45. When the surface tension of the coating is within a suitable range, it is beneficial to maintain the bonding strength between the porous substrate and the coating within a relatively high range, greatly reducing the risk of the coating falling off; it is also beneficial for the electrolyte to infiltrate the isolation membrane, improve the ion transport properties of the isolation membrane, and improve the capacity performance characteristics of the secondary battery.
[0084] During the long-term charge and discharge process of the secondary battery, the volume of the entire battery will increase due to the irreversible changes in the microstructure of the positive electrode active material and the negative electrode active material. In particular, when the secondary battery is quickly charged, the volume of the negative electrode active material after the ions are embedded increases to a greater extent. After the battery expands, it will squeeze and / or stretch the separator, which may easily cause the separator to break, thereby increasing the risk of short circuit between the positive and negative electrodes. Therefore, the separator also needs to have good resistance to external force extrusion. In some embodiments, the coating also includes a filler. The presence of the filler helps the coating to have a stable spatial network structure, thereby improving the ion transport characteristics and heat resistance of the separator; in addition, it can also improve the tensile strength, puncture resistance and external force extrusion resistance of the separator.
[0085] In some embodiments, the filler may include at least one selected from inorganic particles and organic particles.
[0086] In some embodiments, the decomposition temperature of the filler may be above 200° C., so that the filler has the characteristics of good thermal stability and being difficult to decompose, thereby further improving the heat resistance of the isolation film.
[0087] The inorganic particles have the characteristics of high thermal stability and are not easy to decompose, and their surfaces usually have hydroxyl groups, which can easily form a stable spatial network structure with nanocellulose. In some embodiments, the inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of electrochemical reactions.
[0088] Optionally, the inorganic particles having a dielectric constant of 5 or more include boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti nO3 (abbreviated as PLZT, 0<m<1, 0<n<1), Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT), and at least one of their respective modified inorganic particles. Optionally, the modification method of each inorganic particle may be chemical modification and / or physical modification. The chemical modification method includes coupling agent modification (for example, using silane coupling agent, titanate coupling agent, etc.), surfactant modification, polymer grafting modification, etc. The physical modification method may be mechanical force dispersion, ultrasonic dispersion, high energy treatment, etc. The modification treatment can reduce the agglomeration of inorganic particles, thereby enabling them to form a more stable and uniform spatial network structure with nanocellulose; in addition, by selecting coupling agents, surfactants or polymer-modified inorganic particles with specific functional groups, it is also helpful to improve the wetting characteristics of the coating to the electrolyte and improve the bonding strength between the coating and the porous substrate.
[0089] Optionally, the inorganic particles having ion conductivity but not storing ions include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, Lithium Aluminum Titanate Phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum titanate lithium Li x4 La y4 TiO3, Lithium Germanium Phosphate Thiophosphate x5 Ge y5 P z2 S w 、Lithium Nitride Li x6 N y6 、SiS2 glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7. This can further improve the ion transport characteristics of the isolation membrane.
[0090] Optionally, the inorganic particles capable of undergoing electrochemical reaction include at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials and lithium-titanium compounds.
[0091] Organic particles have good thermal stability and are not easy to decompose, thereby improving the heat resistance of the isolation membrane; at the same time, when the internal temperature of the secondary battery reaches the melting point of the organic particles due to overcharge abuse, heat abuse, etc., the organic particles can also melt and be sucked into the micropores of the porous substrate due to capillary action to play a role in closing the holes and breaking the circuit, which is beneficial to ensure that the secondary battery has high safety performance.
[0092] In some embodiments, the organic particles include but are not limited to at least one of polyethylene particles, polypropylene particles, polystyrene particles, cellulose, cellulose modifiers (e.g., carboxymethyl cellulose), melamine resin particles, phenolic resin particles, polyester particles (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), silicone resin particles, polyimide particles, polyamideimide particles, polyaramid particles, polyphenylene sulfide particles, polysulfone particles, polyethersulfone particles, polyetheretherketone particles, polyaryletherketone particles, and copolymers of butyl acrylate and ethyl methacrylate (e.g., cross-linked polymers of butyl acrylate and ethyl methacrylate).
[0093] In some embodiments, optionally, the glass transition temperature of the organic particles may be above 130°C. Thus, when the internal temperature of the secondary battery reaches 130°C, the organic particles will not change from a glassy state to a viscous flow state, thereby ensuring that the isolation film does not shrink drastically. More optionally, the organic particles include but are not limited to at least one of melamine formaldehyde resin particles, phenolic resin particles, polyester particles, silicone resin particles, polyimide particles, polyamideimide particles, polyaramid particles, polyphenylene sulfide particles, polysulfone particles, polyethersulfone particles, polyetheretherketone particles, and polyaryletherketone particles.
[0094] In some embodiments, the content of the filler in the coating may be ≥60wt%, and may be 65wt% to 90wt%, based on the total weight of the coating. This ensures that the coating slurry has a suitable viscosity, which is more conducive to coating; in addition, it is also conducive to the filler and nanocellulose to form a stable spatial network structure, thereby further improving the heat resistance, tensile strength, puncture resistance and external force extrusion resistance of the isolation membrane.
[0095] In some embodiments, the filler includes primary particles, secondary particles or a combination thereof. Optionally, the filler includes at least secondary particles.
[0096] The filler with secondary particle morphology has a smaller particle size, a larger specific surface area, and a better affinity with nanocellulose. At the same time, nanocellulose can also be overlapped in the gaps between the primary particles that constitute the filler with secondary particle morphology, so that the nanocellulose and the filler with secondary particle morphology are overlapped to form an integrated effect. As a result, the coating can have a more stable spatial network structure, thereby further improving the performance of the isolation membrane.
[0097] The filler with primary particle morphology has a larger particle size and higher strength, which can better play a skeleton support role in the coating, reduce the amount of binder, reduce the thermal shrinkage of the isolation membrane and improve the heat resistance of the isolation membrane; and it also helps to make the coating have more pore structure and less water content when the amount is small, which can further improve the ion transmission properties of the isolation membrane and the wetting properties of the electrolyte.
[0098] In some embodiments, the content of the filler in the secondary particle morphology is 50 wt % to 100 wt %, optionally 90 wt % to 99 wt %, based on the total weight of the filler.
[0099] In some embodiments, the average particle size Dv50 of the filler having the primary particle morphology is from 100 nm to 800 nm, and optionally from 200 nm to 400 nm.
[0100] In some embodiments, the average particle size Dv50 of the filler having the secondary particle morphology is ≤200 nm, and can be optionally 50 nm to 200 nm.
[0101] In some embodiments, the filler includes inorganic particles in a primary particle morphology, inorganic particles in a secondary particle morphology, or a combination thereof. Optionally, the filler includes at least inorganic particles in a secondary particle morphology.
[0102] In some embodiments, the crystal form of the inorganic particles of the secondary particle morphology includes at least two of the α-crystal form, the θ-crystal form, the γ-crystal form, and the η-crystal form, and optionally includes at least two of the α-crystal form, the θ-crystal form, and the γ-crystal form.
[0103] The inorganic particles of secondary particle morphology of α crystal form have diffraction peaks at 2θ of 57.48°±0.2° and 43.34°±0.2° in an X-ray diffraction spectrum measured by using an X-ray diffractometer. In some embodiments, the content of α crystal form is ≥1.2wt%, optionally 1.2wt% to 10wt%, and more optionally 1.2wt% to 5wt%, based on the total weight of the inorganic particles of secondary particle morphology.
[0104] The inorganic particles of the secondary particle morphology of the θ crystal form have diffraction peaks at 2θ of 36.68°±0.2° and 31.21°±0.2° in an X-ray diffraction spectrum measured by using an X-ray diffractometer. In some embodiments, the content of the θ crystal form is ≥50wt%, optionally 60wt% to 85wt%, and more optionally 60wt% to 82.5wt%, based on the total weight of the inorganic particles of the secondary particle morphology.
[0105] The inorganic particles of the secondary particle morphology of the γ crystal form have diffraction peaks at 2θ of 66.95°±0.2° and 45.91°±0.2° in an X-ray diffraction spectrum measured by using an X-ray diffractometer. In some embodiments, the content of the γ crystal form is ≥10wt%, optionally 15wt% to 60wt%, and more optionally 15wt% to 35wt%, based on the total weight of the inorganic particles of the secondary particle morphology.
[0106] The inorganic particles of the secondary particle morphology of the η crystal form have diffraction peaks at 2θ of 31.89°±0.2° and 19.37°±0.2° in an X-ray diffraction spectrum measured by using an X-ray diffractometer. In some embodiments, the content of the η crystal form is ≤5wt%, optionally ≤2wt%, and more optionally ≤1wt%, based on the total weight of the inorganic particles of the secondary particle morphology.
[0107] Inorganic particles with secondary particle morphology of α crystal form have the advantages of high hardness, good heat resistance, low dielectric constant, high safety and high true density; Inorganic particles with secondary particle morphology of θ crystal form have moderate specific surface area and hardness, which can better improve the heat resistance and ion transmission characteristics of the isolation membrane at the same time; Inorganic particles with secondary particle morphology of γ crystal form and η crystal form have the advantage of large specific surface area. Therefore, selecting fillers with different crystal forms helps to improve the heat resistance and ion transmission characteristics of the isolation membrane.
[0108] In some embodiments, the crystal forms of the inorganic particles with the secondary particle morphology include α-crystal form, θ-crystal form, γ-crystal form and η-crystal form, and the content of α-crystal form is 1.2wt% to 5wt%, the content of θ-crystal form is 60wt% to 82.5wt%, the content of γ-crystal form is 15wt% to 35wt%, and the content of η-crystal form is ≤1wt%, all based on the total weight of the inorganic particles with the secondary particle morphology.
[0109] The X-ray diffraction spectrum of inorganic particles with secondary particle morphology can be obtained by testing as follows: After drying the inorganic particles with secondary particle morphology, grind them in a mortar (such as an agate mortar) for 30 minutes, and then use an X-ray diffractometer (such as Miniflex600-C) to test and obtain the X-ray diffraction spectrum. During the test, a Cu target material, a Ni filter, a tube voltage of 40KV, a tube current of 15mA, and a continuous scanning range of 5°-80° can be used.
[0110] In some embodiments, the crystal form of the inorganic particles of the primary particle morphology includes at least one of an α crystal form and a γ crystal form, and optionally includes an α crystal form. The inorganic particles of the primary particle morphology of the α crystal form have the advantages of high hardness, good heat resistance, low dielectric constant, high safety and high true density, thereby further improving the heat resistance of the isolation film.
[0111] In some embodiments, the crystal form of the inorganic particles in the primary particle morphology includes α crystal form, and the content of α crystal form is ≥90wt%, optionally 95wt% to 100wt%, based on the total weight of the inorganic particles in the primary particle morphology.
[0112] In some embodiments, the nanocellulose may include at least one of cellulose nanofibers (Cellulose nanofibrils, CNF, also known as nanofibrillated cellulose or microfibrillated cellulose), cellulose nanowhiskers (Cellulose nanocrystals, CNC, also known as cellulose nanocrystals, nanocrystalline cellulose) and bacterial nanocellulose (Bacterial nanocellulose, BNC, also known as bacterial cellulose or microbial cellulose), and cellulose nanowhiskers may be selected. Cellulose nanowhiskers may have a high degree of crystallinity, thereby reducing their hydrophilicity, which is beneficial to the discharge of water during the drying process, so that the coating of the present application can also have a lower moisture content; in addition, cellulose nanowhiskers are also easy to overlap with fillers, so that the coating has a more stable spatial network structure, which can further improve the performance of the isolation membrane.
[0113] In some embodiments, the nanocellulose includes at least one of unmodified nanocellulose (also known as hydroxyl nanocellulose) and modified nanocellulose, and can be modified nanocellulose.
[0114] The modified nanocellulose includes a modification group. In some embodiments, the modification group may include at least one of an amine group, a carboxylic acid group, an aldehyde group, a sulfonic acid group, a boric acid group, and a phosphoric acid group, and may optionally include at least one of a sulfonic acid group, a boric acid group, and a phosphoric acid group.
[0115] The inventors found in further research that when nanocellulose has the above-mentioned specific modified groups, on the one hand, it can effectively improve the heat resistance of the separator and improve the thermal safety performance of the secondary battery. On the other hand, it is also beneficial to keep the bonding strength between the porous substrate and the coating within a high range, greatly reducing the risk of coating shedding. When nanocellulose has the above-mentioned specific modified groups, nanocellulose can also form a more stable spatial network structure with the filler, thereby further improving the ion transport characteristics and voltage breakdown resistance of the separator, which is beneficial to match the high-voltage positive electrode active material and further improve the energy density of the secondary battery. In addition, the presence of the modified group can also reduce the proportion of hydroxyl groups, thereby ensuring that the coating slurry has a suitable viscosity, which is more conducive to coating, thereby also improving the production efficiency of the separator and the uniformity of the coating.
[0116] In some embodiments, the modified nanocellulose includes a hydroxyl group and a modified group, and the molar ratio of the modified group to the hydroxyl group may be 1:4 to 4:1, and may be 2:3 to 7:3. When the molar ratio of the modified group to the hydroxyl group is within a suitable range, the heat resistance and ion transport properties of the separator can be further improved, and the separator can also have high bonding strength.
[0117] The type of modified groups in nanocellulose can be determined by infrared spectroscopy. For example, the infrared spectrum of the material can be tested to determine the characteristic peaks contained therein, thereby determining the type of modified groups. Specifically, the material can be subjected to infrared spectroscopy analysis using instruments and methods known in the art, such as an infrared spectrometer (such as the IS10 Fourier transform infrared spectrometer of Nicolet, USA), and tested according to the general rules for infrared spectroscopy analysis methods of GB / T 6040-2019.
[0118] In some embodiments, the average diameter of the nanocellulose may be ≤40 nm, and may be 10 nm to 35 nm. When the average diameter of the nanocellulose is within a suitable range, the heat resistance of the separator can be further improved, and the heat shrinkage rate of the separator can be reduced.
[0119] In some embodiments, the average length of the nanocellulose may be 100 nm to 600 nm, and may be 200 nm to 500 nm. When the average length of the nanocellulose is within a suitable range, the heat resistance and ion transport properties of the separator can be further improved.
[0120] In some embodiments, the aspect ratio of the nanocellulose may be 5 to 60, and may be 15 to 30. When the aspect ratio of the nanocellulose is within a suitable range, the ion transport properties of the separator can be further improved.
[0121] The average length and average diameter of the nanocellulose can be measured by the following method: a sample of 3.6 mm × 3.6 mm is cut out from any area of the isolation film, and the microscopic morphology of the coating in the sample is mapped using a scanning electron microscope (e.g., ZEISS Sigma 300), and a high vacuum mode is selected, the working voltage is 3 kV, and the magnification is 30,000 times to obtain a SEM image; based on the obtained SEM image, multiple (e.g., more than 5) test areas are selected for length statistics, each test area has a size of 0.5 μm × 0.5 μm, and then the average value of the length obtained from each test area is taken as the average length of the nanocellulose; based on the obtained SEM image, multiple (e.g., more than 5) test areas are selected for diameter statistics using Nano Measurer particle size distribution statistical software, each test area has a size of 0.5 μm × 0.5 μm, and then the average value of the diameter obtained from each test area is taken as the average diameter of the nanocellulose.
[0122] In some embodiments, the weight average molecular weight of the nanocellulose may be 10000 to 60000, and may be 30000 to 50000. When the weight average molecular weight of the nanocellulose is within a suitable range, it can not only prevent the nanocellulose from blocking the pore structure of the separator, but also keep the viscosity of the coating slurry within a reasonable range, thereby improving the fluidity and wettability of the slurry during coating, thereby improving the quality of the coating, and further improving the heat resistance and ion transport properties of the separator.
[0123] In some embodiments, the shape of the nanocellulose may include at least one of the following: tubular (e.g., hollow tubular), fibrous, and rod-shaped. Nanocellulose of suitable shape is more conducive to forming a stable spatial network structure with fillers, thereby further improving the ion transport properties of the isolation membrane.
[0124] In some embodiments, the content of the nanocellulose in the coating may be ≥8wt%, optionally 8wt% to 35wt%, and more optionally 10wt% to 25wt%, based on the total weight of the coating. When the content of nanocellulose is within a suitable range, it can ensure that the coating slurry has a suitable viscosity, which is more conducive to coating. When the content of nanocellulose is within a suitable range, it can also maintain a high bonding strength between the coating and the porous substrate, thereby improving the structural stability of the isolation membrane. In addition, when the content of nanocellulose is within a suitable range, it is also beneficial for nanocellulose and other components (such as fillers, etc.) to build a stable spatial network structure, thereby further enhancing the ion conduction ability, external force extrusion resistance and voltage breakdown resistance of the isolation membrane.
[0125] In some embodiments, the coating may further include a non-granular binder. The present application has no particular restrictions on the type of non-granular binder, and any known material with good adhesion may be selected. Optionally, the non-granular binder includes an aqueous solution binder, which has the advantages of good thermodynamic stability and environmental protection, thereby facilitating the preparation and coating of the coating slurry. As an example, the aqueous solution binder includes at least one of an aqueous solution acrylic resin (e.g., a homopolymer of acrylic acid, methacrylic acid, sodium acrylate monomers or a copolymer with other comonomers), polyvinyl alcohol (PVA), an isobutylene-maleic anhydride copolymer, and polyacrylamide.
[0126] Optionally, the content of the non-granular binder in the coating is less than 1wt%, based on the total weight of the coating. The nanocellulose and filler in the coating of the present application can form a stable spatial network structure, thereby enabling the isolation membrane to maintain high bonding strength and good ion transmission properties while reducing the amount of binder used.
[0127] In some embodiments, the coating does not contain a wetting agent, such as common acrylates and polyoxyethylene-polyoxypropylene block copolymer wetting agents. A wetting agent is generally a compound with low surface tension and high fluidity, which easily leads to the problem of porous substrate pore blocking during the coating slurry coating and drying process. The coating of the present application does not contain a wetting agent, thereby avoiding the problem of porous substrate pore blocking during the coating slurry coating and drying process. The inventors also found in the research process that the coating slurry provided in the present application can have good wettability, thereby eliminating the need for a wetting agent.
[0128] The present application has no particular restrictions on the material of the porous substrate, and any known substrate with good chemical stability and mechanical stability can be selected, such as at least one of glass fiber, non-woven fabric, polyolefin film (such as polyethylene, polypropylene and polyvinylidene fluoride, etc.). The porous substrate can be a single-layer film or a multi-layer composite film. When the porous substrate is a multi-layer composite film, the materials of each layer can be the same or different.
[0129] In some embodiments, the thickness of the porous substrate may be ≤6 μm, and may be 3 μm to 5 μm. The coating of the present application can significantly improve the heat resistance of the separator, thereby allowing a thinner porous substrate to be used, thereby helping to improve the energy density of the secondary battery.
[0130] In some embodiments, the surface density of the coating may be 0.6 g / m 2 Up to 1.5g / m 2 , optional 0.8g / m 2 Up to 1.1g / m 2This makes it possible to obtain an isolation membrane with better heat resistance and ion transport properties.
[0131] In some embodiments, the thickness of the coating layer may be ≤1.5 μm, and may be 0.5 μm to 0.8 μm, thereby helping to improve the energy density of the secondary battery.
[0132] In some embodiments, the isolation film may further include an adhesive layer, which is disposed on at least a portion of the surface of the coating layer, and the adhesive layer includes a granular binder. The adhesive layer can not only prevent the coating layer from falling off and improve the safety performance of the secondary battery, but also improve the interface between the isolation film and the electrode and enhance the cycle performance of the secondary battery.
[0133] Optionally, the granular binder includes at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer. The comonomer includes but is not limited to at least one of an acrylate monomer, an acrylic acid monomer, an olefin monomer, a halogen-containing olefin monomer, a fluoroether monomer, and the like.
[0134] Alternatively, the granular binder includes a vinylidene fluoride based polymer, such as a homopolymer of vinylidene fluoride monomer (VDF) and / or a copolymer of vinylidene fluoride monomer and a comonomer. The comonomer may be at least one of an olefin monomer, a fluorine-containing olefin monomer, a chlorine-containing olefin monomer, an acrylate monomer, an acrylic monomer, and a fluoroether monomer. Alternatively, the comonomer may include at least one of trifluoroethylene (VF3), chlorotrifluoroethylene (CTFE), 1,2-vinylidene fluoride, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), perfluoro (alkyl vinyl) ether (e.g., perfluoro (methyl vinyl) ether PMVE, perfluoro (ethyl vinyl) ether PEVE, perfluoro (propyl vinyl) ether PPVE), perfluoro (1,3-dioxole) and perfluoro (2,2-dimethyl-1,3-dioxole) (PDD).
[0135] In some embodiments, the bonding strength between the coating and the porous substrate is 16 N / m to 40 N / m, and can be 20 N / m to 35 N / m. The separator of the present application has high bonding strength, so that the coating is not easy to fall off during the long-term charge and discharge cycle of the secondary battery, and the safety performance of the secondary battery is better.
[0136] In some embodiments, the longitudinal heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤5%, and may be 0.5% to 3%.
[0137] In some embodiments, the transverse heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤5%, and may be 0.5% to 3%.
[0138] The isolation film of the present application has low thermal shrinkage in both the transverse and longitudinal directions at a high temperature of 150° C., thereby further improving the safety performance of the secondary battery.
[0139] In some embodiments, the longitudinal tensile strength of the separator is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 .
[0140] In some embodiments, the transverse tensile strength of the separator is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 .
[0141] The separator of the present application has high tensile strength in both the transverse and longitudinal directions, so that when the secondary battery expands, the probability of the separator being damaged is low, thereby further improving the safety performance of the secondary battery.
[0142] In some embodiments, the wetted length of the isolation film is ≥30 mm, and can be optionally 30 mm to 80 mm.
[0143] In some embodiments, the wetting speed of the isolation film is ≥3 mm / s, and can be optionally 3 mm / s to 10 mm / s.
[0144] The separator of the present application has good electrolyte infiltration characteristics, thereby being able to improve the ion transport characteristics and capacity performance characteristics of the secondary battery.
[0145] In some embodiments, the air permeability of the isolation membrane is ≤300 s / 100 mL, and can be 100 s / 100 mL to 230 s / 100 mL. The isolation membrane of the present application has good air permeability, thereby improving the ion transmission properties of the isolation membrane.
[0146] In the present application, the average particle size Dv50 of the material has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be tested with a laser particle size analyzer (e.g., Master Size 3000) with reference to GB / T 19077-2016 particle size distribution laser diffraction method.
[0147] In this application, the specific surface area of a material is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method with reference to GB / T 19587-2017, and calculated by BET (BrunauerEmmett Teller) method. Alternatively, the nitrogen adsorption specific surface area analysis test can be performed by Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.
[0148] In the present application, the surface tension of the coating and the porous substrate has a meaning known in the art and can be measured by methods known in the art, for example, by using a dyne pen for testing.
[0149] In the present application, the bonding strength between the coating and the porous substrate has a meaning well known in the art and can be measured by methods known in the art. For example, reference can be made to the standard GB / T 2792-2014, using a tensile tester (such as a high-speed rail tensile machine, the initial clamp spacing can be 40 mm) to perform a 180° peel test at a tensile speed of 50 mm / min, and the bonding strength can be calculated.
[0150] In the present application, the heat shrinkage, tensile strength and air permeability of the isolation film have the meanings known in the art and can be measured by methods known in the art. For example, they can be tested with reference to the standard GB / T 36363-2018.
[0151] In the present application, the wetting length and wetting speed of the isolation membrane have the meanings known in the art and can be measured by methods known in the art. An exemplary test method is as follows: cut the isolation membrane into samples with a width of 5 mm and a length of 100 mm, fix the two ends of the sample and place it horizontally; take 0.5 mg of electrolyte and drop it in the center of the sample. After reaching the specified time (1 min in this application), take a picture and measure the length of the electrolyte diffusion, thereby obtaining the wetting length and wetting speed of the isolation membrane. In order to ensure the accuracy of the test results, multiple (for example, 5 to 10) samples can be taken for testing, and the test results are obtained by calculating the average value. The electrolyte can be prepared as follows: ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a mass ratio of 30:50:20 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0152] It should be noted that the coating parameters (such as surface density, thickness, etc.) of the above-mentioned isolation membrane are all coating parameters of a single side of the porous substrate.
[0153] When the coating is disposed on both sides of the porous substrate, the coating parameters on either side satisfy the present application and are considered to fall within the protection scope of the present application.
[0154] Preparation method
[0155] A second aspect of an embodiment of the present application provides a method for preparing an isolation membrane of the first aspect of an embodiment of the present application, comprising the following steps: S1, providing a porous substrate; S2, providing a coating slurry containing nanocellulose; S3, applying the coating slurry on at least one surface of the porous substrate to form a coating and drying to obtain an isolation membrane, wherein the isolation membrane comprises a porous substrate and a coating arranged on at least one surface of the porous substrate, the surface tension of the porous substrate is δ1mN / m, the surface tension of the coating is δ2mN / m, and the isolation membrane satisfies δ1 / δ2≥0.68.
[0156] In some embodiments, 0.68≤δ1 / δ2≤1.8, 0.7≤δ1 / δ2≤1.5, 0.7≤δ1 / δ2≤1.2, 0.7≤δ1 / δ2≤1.0 or 0.7≤δ1 / δ2≤0.9.
[0157] In some embodiments, in S1, the surface tension δ1mN / m of the porous substrate may satisfy δ1≥23, optionally, 23≤δ1≤45. When the surface tension of the porous substrate is within a suitable range, the coating slurry is not easily leaked during coating, and the porous substrate has a larger coverage area, so that the separator can have better heat resistance and the secondary battery can have better safety performance; at the same time, it is also beneficial to keep the bonding strength between the porous substrate and the coating within a high range, greatly reducing the risk of coating shedding.
[0158] In the present application, porous substrates with different surface tensions can be purchased commercially, and the surface of the porous substrate can be treated with an oxidant or irradiated with ultraviolet light to give it a desired surface tension.
[0159] In some embodiments, in S2, the solvent may be water, such as deionized water.
[0160] In some embodiments, in S2, the coating slurry may further include other components, for example, a binder, a filler, etc. Optionally, the binder includes an aqueous solution binder. Optionally, the filler includes at least secondary particles.
[0161] In some embodiments, in S2, the coating slurry does not use a wetting agent.
[0162] In some embodiments, in S2 , the surface tension of the coating slurry may be 18 mN / m to 52 mN / m.
[0163] In some embodiments, in S2, the solid content of the coating slurry can be controlled between 28% and 45%, for example, between 30% and 38%. When the solid content of the coating slurry is within the above range, the film surface problem of the coating can be effectively reduced and the probability of uneven coating can be reduced, thereby further improving the energy density and safety performance of the secondary battery.
[0164] In some embodiments, in S2, the viscosity of the coating slurry may be 300 mPa·s to 1800 mPa·s, and may be 500 mPa·s to 1300 mPa·s. The viscosity of the coating slurry may be tested using a rotational viscometer.
[0165] In some embodiments, the nanocellulose can be obtained as follows: S21, providing cellulose powder with a whiteness ≥ 80%; S22, mixing the obtained cellulose powder with a modified solution and reacting them, and then washing and removing impurities to obtain cellulose nanowhiskers; S23, adjusting the pH of the obtained cellulose nanowhiskers to neutral (for example, pH 6.5 to 7.5), and obtaining nanocellulose by grinding and cutting.
[0166] Optionally, in S21, the cellulose powder with a whiteness of ≥80% can be purchased from the market, or obtained by chemical methods (such as acid hydrolysis, alkali treatment, Tempo catalytic oxidation), biological methods (such as enzyme treatment), mechanical methods (such as ultrafine grinding, ultrasonic crushing, high-pressure homogenization), etc. The fiber raw material used to prepare the cellulose powder with a whiteness of ≥80% can include plant fibers, such as cotton fibers (such as cotton fibers, kapok fibers), hemp fibers (such as sisal fibers, ramie fibers, jute fibers, flax fibers, hemp fibers, abaca fibers, etc.), palm fibers, wood fibers, bamboo fibers, and grass fibers.
[0167] In some embodiments, the cellulose powder with a whiteness of ≥80% can also be prepared by the following method: after the fiber raw material is loosened and deslagging, it is cooked with an alkali solution (for example, an aqueous solution of NaOH, whose concentration can be 4wt% to 20wt%, optionally 5wt% to 15wt%), and then sequentially washed with water to remove impurities (for example, the number of washings is 3 to 6 times), bleached (for example, sodium hypochlorite and / or hydrogen peroxide can be used), acid washed to remove impurities, washed with water to remove impurities, water driven, and air drying to obtain cellulose powder.
[0168] In some embodiments, in S22, the modified solution may be an acid solution (eg, sulfuric acid aqueous solution, boric acid aqueous solution, phosphoric acid aqueous solution, acetic acid aqueous solution) or an alkaline solution (eg, urea organic solvent solution). Optionally, the modified solution is an acid solution.
[0169] Optionally, the concentration of the acid solution may be 5wt% to 80wt%. When the modified solution is a sulfuric acid aqueous solution, the concentration of the acid solution may be 40wt% to 80wt%, thereby obtaining nanocellulose with a sulfonic acid group. When the modified solution is a boric acid aqueous solution, the concentration of the acid solution may be 5wt% to 10wt%, thereby obtaining nanocellulose with a boric acid group. When the modified solution is a phosphoric acid aqueous solution, the concentration of the acid solution may be 45wt% to 75wt%, thereby obtaining nanocellulose with a phosphoric acid group. When the modified solution is an acetic acid aqueous solution, the concentration of the acid solution may be 40wt% to 80wt%, thereby obtaining nanocellulose with a carboxylic acid group.
[0170] Optionally, the urea organic solvent solution is a urea xylene solution, thereby obtaining nanocellulose having amine groups.
[0171] In some embodiments, in S22, optionally, the mass ratio of the cellulose powder to the modified solution may be 1:2.5 to 1:50, and optionally 1:5 to 1:30.
[0172] When the modification solution is a sulfuric acid aqueous solution, the mass ratio of the cellulose powder to the acid solution may be 1:5 to 1:30. When the modification solution is a boric acid aqueous solution, the mass ratio of the cellulose powder to the acid solution may be 1:20 to 1:50. When the modification solution is a phosphoric acid aqueous solution, the mass ratio of the cellulose powder to the acid solution may be 1:5 to 1:30. When the modification solution is an acetic acid aqueous solution, the mass ratio of the cellulose powder to the acid solution may be 1:5 to 1:30. When the modification solution is a urea organic solvent solution, the mass ratio of the cellulose powder to the urea organic solvent solution may be 1:4 to 1:40.
[0173] In some embodiments, in S22, when the modified solution is an acid solution, the reaction can be carried out at a temperature not higher than 80°C, optionally at 30°C to 60°C, and the reaction time of the cellulose powder and the modified solution can be 0.5h to 4h, optionally 1h to 3h.
[0174] In some embodiments, in S22, when the modified solution is an alkaline solution, the reaction may be performed at 100°C to 145°C, and the reaction time of the cellulose powder and the modified solution may be 1 hour to 5 hours.
[0175] In some embodiments, in S23, grinding can be performed using a grinder, and cutting can be performed using a high-pressure homogenizer. Nanocellulose with different average diameters and / or different average lengths can be obtained by adjusting the grinding parameters (e.g., grinding times, grinding time, etc.) of the grinder and the cutting parameters of the high-pressure homogenizer.
[0176] In some embodiments, in S3, the coating is performed using a coating machine. The present application has no particular restrictions on the model of the coating machine, for example, a commercially available coating machine can be used. The coating machine includes a gravure roller; the gravure roller is used to transfer the coating slurry to the porous substrate.
[0177] In some embodiments, in S3, the coating method may be transfer coating, spin spray coating, dip coating, etc.
[0178] In some embodiments, the method further comprises the following steps: S4, secondary coating: coating a slurry containing a granular binder on at least a portion of the surface of the coating layer, and forming an adhesive layer after drying.
[0179] The preparation method of the isolation film of the present application obtains the coating layer by one-time coating, which greatly simplifies the production process of the isolation film.
[0180] Some parameters such as raw materials and their contents used in the preparation method of the isolation membrane of the present application can refer to the isolation membrane of the first aspect of the implementation method of the present application, and will not be repeated here.
[0181] Unless otherwise specified, all raw materials used in the method for preparing the isolation membrane of the present application can be obtained commercially.
[0182] Secondary battery
[0183] A third aspect of the embodiments of the present application provides a secondary battery.
[0184] Secondary batteries, also known as rechargeable batteries or storage batteries, refer to batteries that can be recharged to activate active materials and continue to be used after the battery is discharged. Generally, secondary batteries include electrode assemblies and electrolytes. The electrode assemblies include positive electrode sheets, negative electrode sheets, and separators. The separators are arranged between the positive electrode sheets and the negative electrode sheets, and mainly play the role of preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through.
[0185] The present application has no particular limitation on the type of secondary battery. For example, the secondary battery may be a lithium ion battery, a sodium ion battery, etc. In particular, the secondary battery may be a lithium ion secondary battery.
[0186] The secondary battery of the third aspect of the embodiment of the present application comprises the separator of the first aspect of the embodiment of the present application or the separator prepared by the method of the second aspect of the embodiment of the present application, and the separator is spaced between the positive electrode sheet and the negative electrode sheet. Optionally, at least one side of the separator close to the negative electrode sheet has the coating of the present application. Thus, the secondary battery of the present application can take into account high energy density, high thermal safety performance and long service life.
[0187] [Positive electrode]
[0188] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0189] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material may include but is not limited to at least one of a lithium-containing transition metal oxide, a lithium-containing phosphate and their respective modified compounds. Examples of the lithium transition metal oxide may include but are not limited to at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and their respective modified compounds. Examples of the lithium-containing phosphate may include but are not limited to at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon and their respective modified compounds.
[0190] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Co c M d O e A f At least one of lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M is selected from at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A is selected from at least one of N, F, S and Cl.
[0191] As an example, the positive electrode active material for lithium ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 At least one of O2, LiFePO4, and LiMnPO4.
[0192] When the secondary battery of the present application is a sodium ion battery, the positive electrode active material may include but is not limited to at least one of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.
[0193] As an example, the positive electrode active material for sodium ion batteries may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials, general formula X p M' q (PO4) r O x Y 3-x In the general formula X p M' q (PO4) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X is selected from H + , Li + 、Na + , K + and NH4 + At least one of, M' is a transition metal cation, optionally at least one of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, optionally at least one of F, Cl and Br.
[0194] In the present application, the modified compound of each positive electrode active material mentioned above may be a compound obtained by doping and / or surface coating the positive electrode active material.
[0195] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode conductive agent is ≤5%.
[0196] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. The present application has no particular restrictions on the type of the positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode binder is ≤5%.
[0197] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0198] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0199] [Negative electrode]
[0200] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0201] The negative electrode active material may be a negative electrode active material for a secondary battery known in the art. As an example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide, and tin alloy material.
[0202] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total mass of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤5%.
[0203] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, based on the total mass of the negative electrode film layer, the mass percentage of the negative electrode binder is ≤5%.
[0204] In some embodiments, the negative electrode film layer may further include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, etc. In some embodiments, based on the total mass of the negative electrode film layer, the mass percentage of the other additives is ≤2%.
[0205] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0206] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0207] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the present application also includes a conductive primer layer (for example, composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode plate described in the present application also includes a protective layer covering the surface of the negative electrode film layer.
[0208] [Electrolyte]
[0209] During the charge and discharge process of the secondary battery, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to actual needs.
[0210] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not specifically limited and can be selected according to actual needs.
[0211] When the secondary battery of the present application is a lithium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0212] When the secondary battery of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0213] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0214] In some embodiments, the electrolyte may further include additives, for example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature power performance, etc.
[0215] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process and / or a lamination process.
[0216] In some embodiments, the secondary battery may include an outer package, which may be used to package the electrode assembly and the electrolyte.
[0217] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0218] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0219] In some embodiments, Figure 2 As shown, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate are enclosed to form a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0220] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and a secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0221] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0222] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0223] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0224] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0225] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0226] Electrical devices
[0227] The fourth aspect of the embodiment of the present application provides an electric device, which includes at least one of the secondary battery, battery module or battery pack of the present application. The secondary battery, battery module or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0228] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0229] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0230] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0231] Example
[0232] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations can be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0233] Preparation of Nanocellulose C1
[0234] Cellulose powder preparation
[0235] The cotton linters were opened and deslagging by a cotton opener, and then boiled at 150°C for 2 hours using a 5wt% NaOH aqueous solution. The cotton linters were then washed with water to remove impurities (the number of washings was 3 times), bleached with sodium hypochlorite, washed with dilute hydrochloric acid to remove impurities, washed with water to remove impurities (the number of washings was 1 time), driven out of water, and dried with air flow to obtain cotton cellulose powder with a whiteness of ≥85%.
[0236] Esterification of cellulose
[0237] 1 kg of the obtained cotton cellulose powder was mixed with 30 kg of a 60 wt % sulfuric acid aqueous solution and reacted at 60° C. for 1.5 h. After the reaction, the mixture was sequentially washed with water to remove impurities (washed 3 times), filtered, and deacidified to remove impurities, thereby obtaining cellulose nano whiskers with sulfonic acid modified groups.
[0238] Neutralization of cellulose
[0239] The pH of the cellulose nanowhiskers with sulfonic acid modified groups was first adjusted to neutral with a 10 wt % NaOH aqueous solution, and then dispersed with a grinder at high speed for 2.5 h, the grinding times were 2 times, and then nano-scale cutting was performed using a high-pressure homogenizer to obtain nanocellulose C1 with sulfonic acid modified groups with an average length of 475 nm and an average diameter of 25 nm, and the molar ratio of sulfonic acid group to hydroxyl group was 5:3.
[0240] Preparation of Nanocellulose C2 to C10
[0241] Nanocelluloses C2 to C10 were prepared in a similar manner to nanocellulose C1, with the differences shown in Table 1. During the preparation process, nanocelluloses with different average diameters and / or different average lengths can be obtained by adjusting the processing parameters of the grinder and the cutting parameters of the high-pressure homogenizer.
[0242] Preparation of Nanocellulose C11
[0243] Cellulose powder preparation
[0244] After the cotton linters are opened and deslagging by a cotton opener, they are cooked at 150°C for 2 hours using a 5wt% NaOH aqueous solution, and then sequentially washed and removed (washed 3 times), bleached with sodium hypochlorite, washed and removed with dilute hydrochloric acid, washed and removed with water (washed once), driven out of water, and dried with air flow to obtain cotton cellulose powder with a whiteness of ≥85%. At 10°C, the obtained cotton cellulose powder is mixed with a 20wt% NaOH aqueous solution, stirred for 2 hours, filtered, and washed twice to obtain alkali cellulose powder.
[0245] Esterification of cellulose
[0246] 50 g of the obtained alkali cellulose powder and 200 g of urea were placed in a three-mouth reactor with an oil-water separator. After the urea was dissolved, 5 g of xylene was added and the temperature was raised to 137°C under stirring. The reaction was terminated after 4 hours. Then, the mixture was washed with water (washed 3 times), filtered and dried to obtain cellulose carbamate.
[0247] Neutralization of cellulose
[0248] The obtained cellulose carbamate was dissolved in a 5 wt % NaOH aqueous solution to obtain a uniform cellulose carbamate solution, which was then dispersed by a grinder at high speed for 2.5 h, the grinding times being 2 times, and then nano-scale cutting was performed using a high-pressure homogenizer to obtain nanocellulose with an average length of 475 nm and an average diameter of 25 nm having amino-modified groups, and the molar ratio of amino groups to hydroxyl groups was 4:3.
[0249] The molar ratio of the modified group to the hydroxyl group can be measured by the following method: the hydroxyl value (the number of milligrams of potassium hydroxide equivalent to the hydroxyl content in each gram of the sample) of the raw cellulose and the modified nanocellulose is measured according to the phthalic anhydride method in GB / T 12008.3-2009, and the numerical unit obtained is mg KOH / g, which is converted into mmol / g as the hydroxyl content. The content of the modified group (i.e. the content of the modified hydroxyl group) is obtained by subtracting the hydroxyl content of the modified nanocellulose from the hydroxyl content of the raw cellulose, and the molar ratio of the modified group to the hydroxyl group is calculated.
[0250] Preparation of Nanocellulose C12 and C13
[0251] Unmodified nanocellulose, product model CNWS-50, purchased from Zhongke Leiming (Beijing) Technology Co., Ltd., can be further processed using a grinder and / or a high-pressure homogenizer to obtain nanocellulose with different average diameters and / or different average lengths. See Table 1 for details.
[0252] Table 1
[0253]
[0254] Example 1
[0255] (1) Preparation of isolation membrane
[0256] S1, providing a PE porous substrate: thickness of 5 μm, surface tension of 25 mN / m.
[0257] S2, preparing coating slurry: the above-prepared nanocellulose C1, filler alumina (secondary particle morphology, average particle size Dv50 is 160nm), and binder aqueous solution type polyacrylic acid are mixed uniformly in a proper amount of solvent deionized water in a mass ratio of 15:84.1:0.9 to obtain a coating slurry with a solid content of 35wt% and a viscosity of 854mPa·s.
[0258] S3, coating: the prepared coating slurry is coated on both surfaces of the PE porous substrate by a coating machine, and a separator is obtained through drying and slitting processes. The thickness of the coating on one side of the PE porous substrate is 0.8 μm.
[0259] (2) Preparation of positive electrode sheet
[0260] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) according to a mass ratio of 96.2:2.7:1.1 to obtain positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, striping, cutting and other processes. The surface density of the positive electrode sheet is 0.207mg / mm 2 , compacted density is 3.5g / cm 3 .
[0261] (3) Preparation of negative electrode sheet
[0262] The negative electrode active material artificial graphite, conductive agent carbon black (Super P), binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed evenly in a proper amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through drying, cold pressing, striping and cutting processes. The surface density of the negative electrode sheet is 0.126mg / mm 2 , compacted density is 1.7g / cm 3 .
[0263] (4) Preparation of electrolyte
[0264] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed at a mass ratio of 30:70 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0265] (5) Preparation of secondary batteries
[0266] The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a secondary battery is obtained.
[0267] Embodiment 2-6
[0268] The secondary battery was prepared by a method similar to that of Example 3, except that the surface tension of the porous substrate used in the preparation of the separator was different, and the specific parameters are shown in Table 2. Porous substrates with different surface tensions can be purchased commercially, and the surface of the porous substrate can also be treated with an oxidant or irradiated with ultraviolet light to give it a desired surface tension.
[0269] Embodiment 7-17
[0270] The secondary battery was prepared by a method similar to that of Example 3, except that different types of nanocellulose were used in the preparation of the isolation membrane. Specific parameters are shown in Tables 1 and 2.
[0271] Examples 18-20
[0272] The secondary battery was prepared by a method similar to that of Example 3, except that different amounts of nanocellulose and filler were added in the preparation of the isolation membrane. Specific parameters are shown in Table 2.
[0273] Examples 21-22
[0274] The secondary battery is prepared by a method similar to that in Example 3, except that the filler in the preparation of the isolation membrane is a mixture of secondary particle morphology of alumina (average particle size Dv50 is 160nm) and primary particle morphology of alumina (average particle size Dv50 is 400nm), and the mass ratio of the two in Example 21 is 90:10, and the mass ratio of the two in Example 22 is 70:30.
[0275] Comparative Example 1
[0276] The secondary battery was prepared by a method similar to that of Example 3, except that the preparation parameters of the isolation membrane were different, the surface tension of the PE porous substrate was 20 mN / m, the nanocellulose used was unmodified nanocellulose numbered C12, and the filler used was alumina with a primary particle morphology and an average particle size Dv50 of 1000 nm.
[0277] Comparative Example 2
[0278] The secondary battery was prepared by a method similar to that of Example 3, except that the surface tension of the PE porous substrate in the preparation of the separator was 20 mN / m, and no filler was added to the coating slurry.
[0279] Comparative Example 3
[0280] The secondary battery was prepared by a method similar to that of Example 3, except that the surface tension of the PE porous substrate in the preparation of the isolation membrane was 20 mN / m, and the filler was alumina in primary particle morphology with an average particle size Dv50 of 400 nm.
[0281] Comparative Example 4
[0282] The secondary battery was prepared by a method similar to that of Example 3, except that the surface tension of the PE porous substrate in the preparation of the separator was 20 mN / m.
[0283] Table 2
[0284]
[0285]
[0286] Test Section
[0287] (1) Viscosity test of coating slurry
[0288] The viscosity of the coating slurry is tested using a rotational viscometer at 25° C. The test instrument may be an AMETEK rotational viscometer with a rotation speed of 12 r / min.
[0289] (2) Surface tension of coating and porous substrate
[0290] The test was carried out at 25°C using a dyne pen.
[0291] (3) Bond strength test between coating and porous substrate
[0292] At 25°C, a tensile tester is used to test the bonding strength between the coating and the porous substrate in the isolation film. The isolation film sample size can be 100mm×15mm, the isolation film peeling speed can be 50mm / min, the peeling angle can be 180°, the tensile tester can be a high-speed rail tensile machine, and the starting clamp spacing can be 40mm. The test standard can refer to GB / T 2792-2014.
[0293] (4) Thermal shrinkage test of isolation film
[0294] Sample preparation: The isolation film prepared above was punched into samples with a width of 50 mm and a length of 100 mm using a punching machine. Five parallel samples were placed on A4 paper and fixed. The A4 paper containing the samples was then placed on corrugated paper with a thickness of 1 mm to 5 mm.
[0295] Sample test: Set the temperature of the blast oven to 150°C. After the temperature reaches the set temperature and stabilizes for 30 minutes, put the A4 paper placed on the corrugated paper into the blast oven and start timing. After the set time (1 hour in this application) is reached, measure the length and width of the isolation film, and mark the values as a and b respectively.
[0296] Calculation of thermal shrinkage: longitudinal (MD) thermal shrinkage = [(100-a) / 100] × 100%, transverse (TD) thermal shrinkage = [(50-b) / 50] × 100%, and the average value of 5 parallel samples is taken as the test result.
[0297] (5) Air permeability test of isolation film
[0298] At 25°C, measure the time required for 100 mL of air to pass through the isolation membrane, and take the average value of 5 parallel samples as the test result. The test instrument can be the Xionggu KRK Wangyan air permeability tester.
[0299] (6) Cycle performance test of secondary batteries
[0300] At 25°C, charge the secondary battery to 4.2V at 1C constant current, and continue to charge at constant voltage until the current is ≤0.05C. At this time, the secondary battery is fully charged. Record the charging capacity at this time, which is the charging capacity of the first cycle; after the secondary battery is left to stand for 5 minutes, discharge it to 2.8V at 1C constant current. This is a cyclic charge and discharge process. Record the discharge capacity at this time, which is the discharge capacity of the first cycle. Perform cyclic charge and discharge tests on the secondary battery according to the above method, and record the discharge capacity after each cycle. The capacity retention rate (%) of the secondary battery after 500 cycles at 25°C = discharge capacity after 500 cycles / discharge capacity of the first cycle × 100%.
[0301] (7) Hot box test of secondary batteries
[0302] At 25°C, charge the secondary battery to 4.2V at 1C constant current, continue to charge at constant voltage until the current is ≤0.05C, and stand for 5 minutes. Then test each secondary battery with a fixture in the DHG-9070A DHG series high temperature oven, and heat it from room temperature to 100±2°C at a rate of 5°C / min, and keep it for 30 minutes; then heat it at a rate of 5°C / min, and keep it warm for 30 minutes every time the temperature rises by 5°C, until the secondary battery fails. Monitor the change in the surface temperature of the secondary battery during the heating process. When the temperature starts to rise sharply, the corresponding oven temperature is the hot box failure temperature of the secondary battery. The higher the hot box failure temperature of the secondary battery, the better the thermal safety performance of the secondary battery.
[0303] Table 3
[0304]
[0305] As can be seen from Table 3, in Examples 1-22, by arranging a coating containing nanocellulose on both surfaces of the porous substrate of the isolation membrane, and reasonably controlling the surface tension δ1mN / m of the porous substrate and the surface tension δ2mN / m of the coating so that they satisfy δ1 / δ2≥0.68, optionally satisfy 0.68≤δ1 / δ2≤1.8, and more optionally satisfy 0.7≤δ1 / δ2≤1.2, the isolation membrane can have low thermal shrinkage, high viscosity strength and high air permeability, and the secondary battery can have high thermal safety performance and good cycle performance.
[0306] The aluminum oxide used in the coating of Comparative Example 1 is in the form of primary particles and has a relatively large particle size. At this time, the aluminum oxide and the nanocellulose cannot form an integrated overlapping effect, which leads to poor heat resistance of the separator and thermal safety performance of the secondary battery. In addition, when preparing the coating slurry in Comparative Example 1, a relatively high content of binder is required, and when the amount of binder is relatively large, pore blocking is prone to occur, which also leads to poor cycle performance of the secondary battery.
[0307] In Comparative Example 2, aluminum oxide is not used in the coating. At this time, the viscosity of the nanocellulose solution is relatively high, resulting in poor air permeability of the coating and poor cycle performance of the secondary battery. At the same time, the heat resistance of the isolation membrane and the thermal safety performance of the secondary battery are also poor.
[0308] The ratio of the surface tension of the porous substrate used in Comparative Examples 3 and 4 to the surface tension of the prepared coating is less than 0.68. At this time, there is a large-area coating leakage problem when the coating slurry is applied, which results in poor bonding strength and heat resistance of the isolation film, and the thermal safety performance of the secondary battery is also poor.
[0309] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A separator comprising a porous substrate and a coating disposed on at least one surface of the porous substrate, wherein: The coating layer includes nanocellulose, the surface tension of the porous substrate is δ1 mN / m, the surface tension of the coating layer is δ2 mN / m, and the isolation membrane satisfies δ1≥23 and 25≤δ2≤50.
2. The isolation film according to claim 1, wherein: 23≤δ1≤45, optionally, 25≤δ1≤45; and / or, 30≤δ2≤45, optionally, 30≤δ2≤43.
3. The isolation film according to claim 1 or 2, wherein: 0.68≤δ1 / δ2≤1.8, optionally, 0.7≤δ1 / δ2≤1.
2.
4. The isolation film according to any one of claims 1 to 3, wherein: The nanocellulose comprises at least one of unmodified nanocellulose and modified nanocellulose, and can be modified nanocellulose. Optionally, the modified nanocellulose comprises a modification group, and the modification group comprises at least one of an amine group, a carboxylic acid group, an aldehyde group, a sulfonic acid group, a boric acid group and a phosphoric acid group, and more optionally comprises at least one of a sulfonic acid group, a boric acid group and a phosphoric acid group; and / or, Optionally, the modified nanocellulose comprises hydroxyl groups and modifying groups, and a molar ratio of the modifying groups to the hydroxyl groups is 1:4 to 4:1, and more preferably 2:3 to 7:
3.
5. The isolation film according to any one of claims 1 to 4, wherein: The nanocellulose satisfies at least one of the following conditions (1) to (3): (1) The average diameter of the nanocellulose is ≤40 nm, and can be selected from 10 nm to 35 nm; (2) The average length of the nanocellulose is 100 nm to 600 nm, and can be optionally 200 nm to 500 nm; (3) The aspect ratio of the nanocellulose is 5 to 60, and can be optionally 15 to 30.
6. The isolation film according to any one of claims 1 to 5, wherein: The content of the nanocellulose in the coating is ≥8 wt %, optionally 10 wt % to 25 wt %, based on the total weight of the coating.
7. The isolation film according to any one of claims 1 to 6, wherein: The coating layer further includes a filler, and the filler includes at least one selected from inorganic particles and organic particles.
8. The isolation film according to claim 7, wherein: The content of the filler in the coating is ≥60 wt %, optionally 65 wt % to 90 wt %, based on the total weight of the coating.
9. The isolation film according to claim 7 or 8, wherein: The filler includes primary particles, secondary particles or a combination thereof, and optionally, the filler includes at least secondary particles; Optionally, the average particle size Dv50 of the filler in the primary particle morphology is 100 nm to 800 nm, and more preferably 200 nm to 400 nm; Optionally, the average particle size Dv50 of the filler with secondary particle morphology is ≤200 nm, and more optionally 50 nm to 200 nm.
10. The isolation film according to any one of claims 7 to 9, wherein: The filler includes inorganic particles in the form of primary particles, inorganic particles in the form of secondary particles, or a combination thereof. Optionally, the filler includes at least inorganic particles in the form of secondary particles. Optionally, the crystal form of the inorganic particles of the primary particle morphology includes at least one of an α crystal form and a γ crystal form, and more optionally includes an α crystal form; Optionally, the crystal form of the inorganic particles of the secondary particle morphology includes at least two of the α crystal form, the θ crystal form, the γ crystal form and the η crystal form, and more optionally includes at least two of the α crystal form, the θ crystal form and the γ crystal form.
11. The isolation film according to any one of claims 1 to 10, wherein: The coating also includes a non-particulate binder; Optionally, the non-granular binder comprises an aqueous solution binder; Optionally, the content of the non-particulate binder in the coating is less than 1 wt %, based on the total weight of the coating.
12. The isolation film according to any one of claims 1 to 11, wherein: The coating does not contain a wetting agent.
13. The isolation film according to any one of claims 1 to 12, wherein: The thickness of the porous substrate is ≤6 μm, and can be 3 μm to 5 μm; and / or, The surface density of the coating is 0.6 g / m 2 Up to 1.5g / m 2 , optional 0.8g / m 2 Up to 1.1g / m 2 and / or, The thickness of the coating is ≤1.5 μm, and can be optionally 0.5 μm to 0.8 μm.
14. The isolation film according to any one of claims 1 to 13, wherein: The isolation film also includes an adhesive layer, which is arranged on at least a portion of the surface of the coating, and the adhesive layer includes a granular binder. Optionally, the granular binder includes at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer.
15. The isolation film according to any one of claims 1 to 14, wherein: The isolation film satisfies at least one of the following conditions (1) to (8): (1) The bonding strength between the coating and the porous substrate is 16 N / m to 40 N / m, and can be 20 N / m to 35 N / m; (2) The longitudinal heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤5%, and can be selected from 0.5% to 3%; (3) The transverse heat shrinkage rate of the isolation film at 150° C. for 1 hour is ≤5%, and can be selected from 0.5% to 3%; (4) The longitudinal tensile strength of the isolation film is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 ; (5) The transverse tensile strength of the isolation film is ≥ 2000 kg / cm 2 , optional 2500kg / cm 2 Up to 4500kg / cm 2 ; (6) The wetted length of the isolation film is ≥30 mm, and can be selected from 30 mm to 80 mm; (7) The wetting speed of the isolation film is ≥3 mm / s, and can be selected from 3 mm / s to 10 mm / s; (8) The air permeability of the isolation membrane is ≤300s / 100mL, and can be optionally 100s / 100mL to 230s / 100mL.
16. A method for preparing the isolation film according to any one of claims 1 to 15, comprising the following steps: S1, providing a porous substrate; S2, providing a coating slurry containing nanocellulose; S3, applying the coating slurry on at least one surface of the porous substrate to form a film layer and drying it to obtain an isolation membrane, wherein the isolation membrane comprises a porous substrate and a coating disposed on at least one surface of the porous substrate, the surface tension of the porous substrate is δ1mN / m, the surface tension of the coating is δ2mN / m, and the isolation membrane satisfies δ1≥23 and 25≤δ2≤50.
17. The method according to claim 16, wherein: The coating slurry also includes a filler.
18. The method according to claim 16 or 17, wherein: The surface tension of the coating slurry is 18 mN / m to 52 mN / m.
19. The method according to any one of claims 16 to 18, further comprising the following steps: S4, secondary coating: coating a slurry containing a granular binder on at least a portion of the surface of the coating layer, and forming an adhesive layer after drying. 20 . A secondary battery comprising the separator according to claim 1 or the separator prepared by the method according to claim 16 .
21. An electrical device comprising the secondary battery according to claim 20.